Glycerol-derived organic carbonates: environmentally friendly plasticizers for PLA - Seo, Hyeon Jeong; Seo, Yeong Hyun; Park, Sang Uk; Lee, Hyun Ju; Lee, Mi Ryu; Park, Jun Hyeong; Cho, Woo Yeon; Lee, Pyung Cheon; Lee, Bun Yeoul (RSC Advances, 2024)
Polylactic acid (PLA) stands as a promising material, sourced from renewables and exhibiting biodegradability—albeit under stringent industrial composting settings. A primary challenge impeding PLA's broad applications is its inherent brittleness, as it fractures with minimal elongation despite its commendable tensile strength. A well-established remedy involves blending PLA with plasticizers. In this study, a range of organic carbonates—namely, 4-ethoxycarbonyloximethyl-[1,3]dioxolan-2-one (1), 4-methoxycarbonyloximethyl-[1,3]dioxolan-2-one (2), glycerol carbonate (3), and glycerol 1-acetate 2,3-carbonate (4)—were synthesized on a preparative scale (∼100 g), using renewable glycerol and CO2-derived diethyl carbonate (DEC) or dimethyl carbonate (DMC). Significantly, 1-4 exhibited biodegradability under ambient conditions within a week, ascertained through soil exposure at 25 °C—outpacing the degradation of comparative cellulose. Further investigations revealed 1's efficacy as a PLA plasticizer. Compatibility with PLA, up to 30 phr (parts per hundred resin), was verified using an array of techniques, including DSC, DMA, SEM, and rotational rheometry. The resulting blends showcased enhanced ductility, evident from tensile property measurements. Notably, the novel plasticizer 1 displayed an advantage over conventional acetyltributylcitrate (ATBC) in terms of morphological stability. Slow crystallization, observed in PLA/ATBC blends over time at room temperature, was absent in PLA/1 blends, preserving amorphous domain dimensions and mitigating plasticizer migration—confirmed through DMA assessments of aged and unaged specimens. Nevertheless, biodegradation assessments of the blends revealed that the biodegradable organic carbonate plasticizers did not augment PLA's biodegradation. The PLA in the blends remained mostly unchanged under ambient soil conditions of 25 °C over a 6 month period. This work underscores the potential of organic carbonates as both eco-friendly plasticizers for PLA and as biodegradable compounds, contributing to the development of environmentally conscious polymer systems.
Keywords: Ambient conditions; Broad application; Diethyl carbonates; Dimethyl carbonate; Glycerol carbonate; Organic carbonates; Renewables; Soil exposure; Stringents; Synthesised